The effectiveness of a training program using mental maps in developing the spatial visual intelligence of the student in the course of learning difficulties - Ali, Sayed Ibrahim; Thabet, Essam Mahmoud Mohamed (Journal of Educational and Psychological Sciences, 2018)
The present study aimed to identify the effect of the use of mental maps in the development of visual spatial intelligence of the student teacher in the Department of Special Education (learning disabilities), Faculty of Education, King Faisal University. The researchers used the semi-experimental method. A sample of 60 students from the seventh and eighth level was selected in the bachelor's degree and were divided into 30 students as a control group and 30 students as an experimental group. The tools used were the visual spatial intelligence test, and a program for the development of visual intelligence spatial by using mind maps. The results of the study showed that there was a statistically significant difference at the level of (0.05) in the mean scores for experimental group in pre (mean = 11.50) and post (mean = 19.10) measurement in favor of post measurement, there was a statistically significant difference at the level of (0.05) in the mean score between control (mean =11.33) and experimental groups (mean = 19.10) in post measurement in favor of experimental group, also revealed the effectiveness of the use of mental maps in the development of spatial visual intelligence among the students in the course of learning difficulties at the Faculty of Education, King Faisal University.
Keywords: mental maps; visual-spatial intelligence; learning difficulties; King Faisal University; special education